A gradient-based method to guard against system degradation in robust parameter design. (19th October 2011) - Loeffelholz, Bernard Jacob; Bauer, Kenneth W.
Robust parameter design (RPD) can be implemented in systems in which a user, through the setting of the levels of controllable factors, seeks to minimise the variability of a system response influenced by uncontrollable factors while obtaining a consistent and reliable system response over time. RPD is conducted under the assumption that the relationship between the system response and controllable and uncontrollable variables does not change over time. Since performance degradation in real-world systems will almost certainly occur; this assumption will inevitably be violated. We propose a methodology to find new levels of controllable factor settings that will be robust to moderate system degradation while remaining robust to noise variables within the system. A gradient-search algorithm is presented for this enhanced RPD analysis utilising quadratic regression.